Lambda and Antiambda production in central Pb-Pb collisions at 40, 80, and 158A GeV - Antičić, Tome (Array, 2004)
Production of Lambda and Antilambda hyperons was measured in central Pb-Pb collisions at 40, 80, and 158 A GeV beam energy on a fixed target. Transverse mass spectra and rapidity distributions are given for all three energies. The Lambda/pi ratio at mid-rapidity and in full phase space shows a pronounced maximum between the highest AGS and 40 A GeV SPS energies, whereas the Antilambda/pi ratio exhibits a monotonic increase.